Determination of the thermoelectric parameters of materials forming part of generator thermoelectric modules - Anatychuk, L.I.; Lysko, V.V. (Journal of Thermoelectricity, 2021)
A method is proposed for determining the thermoelectric parameters of materials forming part of generator thermoelectric modules. A detailed physical model of this method is considered and the results of estimating possible values of errors are presented. The effectiveness of various methods for reducing errors, in particular, the use of gradient radiation shields and thermal switches, has been studied. Bibl. 8, Fig 6, Table 1.